The Impact of Metacognitive Strategies on Students' Expository Reading Comprehension Achievement - Daniswara, Aptana Agra; Devanti, Yeni Mardiyana; Nuraini, Kristi (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2025)
This study aimed to examine the effect of applying metacognitive strategies on the expository reading comprehension achievement of vocational high school students. The research utilized a quasi-experimental design with a pre-test-post-test control group model, involving 32 eleventh-grade students at SMKS Muhammadiyah Jember. The experimental group (n=16) received an intervention consisting of metacognitive strategy instruction facilitated by a reflection table, while the control group (n=16) followed conventional instruction. Data were collected through reading comprehension tests and analyzed using the Wilcoxon Signed-Rank Test due to the non-normal distribution of the control group's post-test data. The findings revealed a statistically significant improvement in the experimental group from pre-test to post-test (p=0.002), whereas no significant change was observed in the control group (p=0.101). It is concluded that metacognitive strategies, particularly when implemented with a structured reflection tool, are a highly effective intervention for improving expository text comprehension in the vocational education context